Rozgraniczenie statutu rzeczowego i kontraktowego przy poszukiwaniu prawa właściwego do oceny zastrzeżenia prawa własności - Kozioł, Agata (Problemy Prawa Prywatnego Międzynarodowego, 2020)
Retention of title as a security on tangible assets is well known in many legal systems. It enables to strengthen the position of the seller in such a contract of sale in which the payment of the price is agreed to be done later than the handing over the good. This instrument disturbs the traditional model of sale in two ways. Firstly, the conclusion of the contract is not directly followed — which takes usually place — by the performance of the obligation to transfer the property. Secondly, the right of property receives in that way a new role to play — it becomes a security right, guarantying the pecuniary claim of the seller and ceases the function of the principal right. In order to find the law applicable to the retention of title, its different aspects — contractual and real — should be qualified according to their nature. These aspects should be treated separately and be assessed according to the proper legal system. For example, the law applicable to contractual assets of retention of title defines if such belated transfer of ownership affects any general rights and obligations of parties, such as the right to receive benefits from the asset or to bear costs of its maintenance. On the other hand, the law of actual location of the asset as a law applicable to real aspects of the retention of title defines the nature of the element disturbing the transfer of ownership and the scope of rights of the seller towards charged good as its owner.